Sirtuin 4 accelerates heart failure development by enhancing reactive oxygen species-mediated profibrotic transcriptional signaling - Byrne, Nikole J.; Koentges, Christoph; Khan, Elisabeth; Pfeil, Katharina; Sandulescu, Robert; Bakshi, Sayan; Költgen, Carolin; Vosko, Ivan; Gollmer, Johannes; Rathner, Thomas; Roth, Günter; Hoffmann, Michael M.; et al. (Journal of Molecular and Cellular Cardiology Plus (Online), 2025)
Sirtuin 4 (SIRT4) is a mitochondrially-localized stress-responsive NAD+-dependent deacetylase predominantly regulating energy metabolism and reactive oxygen species (ROS) homeostasis. Overexpression of SIRT4 aggravates angiotensin-induced cardiac hypertrophy, however underlying mechanisms remain incompletely elucidated. To current study was designed to explore mechanisms underlying adverse effects of increased SIRT4 levels in the heart following pressure overload. Mice with cardiomyocyte-specific overexpression of Sirt4 (cSirt4-Tg) or non-transgenic controls underwent transverse aortic constriction (TAC) or sham procedure. Cardiac structure, function and energy metabolism were assessed by echocardiography and working heart perfusions. Transcriptome analysis was performed using RNA sequencing. Nine weeks following TAC and thereafter, cSirt4-Tg mice displayed exacerbated cardiac dilation, dysfunction, and fibrosis compared to non-transgenic controls. This aggravation was accompanied by impaired rates of glycolysis and a blunted increase of mitochondrial respiratory capacity. More importantly, expression of numerous genes encoding collagens and profibrotic regulators was elevated. This profibrotic signaling was reversed by mitochondria-targeted antioxidant treatment using MitoQ, along with attenuation of cardiac dysfunction and reversal of structural remodeling. SIRT4 may drive oxidative stress and fibrotic signaling via increased NOX4 expression (>7-fold), and/or direct modulation of potential SIRT4 targets newly identified by Human Protein Microarray, including calcitonin gene-related peptide receptor component protein, cyclophilin A, and interleukin-2 receptor β. SIRT4 overexpression accelerates heart failure development in response to pressure overload, predominantly by ROS-mediated enhancement of profibrotic transcriptional signaling. [Display omitted] •SIRT4 overexpression aggravates myocardial oxidative stress, fibrosis, and dysfunction following chronic pressure overload.•SIRT4 overexpression promotes upregulation of genes encoding collagens and profibrotic regulators in response to pressure overload.•SIRT4-driven worsening of cardiomyopathy depends on mitochondrial ROS and profibrotic transcriptional programming.•A Human Protein Microarray identified 14 new potential SIRT4 targets.